Secure information dissemination in heterogeneous wireless sensor networks - Kumar, Kamal (My University, 2014)
With wide spread of sensor technology in every sphere of life and ever increasing digitization one can imagine that soon world will be patched with small sized devices all around. These devices are capable of monitoring and surveillance including an access to vast digital world of information. Seamless transmission using wireless medium, based on anywhere, anytime, anyhow paradigm is a boon for searching data and information as well as processing queries. Deployments of such sensor nodes are not easy, it may range from underwater to mountain, from large dessert to dense forests it is difficult to setup infrastructure for communication. With miniaturization of wireless devices which can receive, send and process information and commands, sensor networks came into existence, inheriting most of features, applications and limitations from ad hoc networks, the sensor networks exhibit their own area of applications. Primarily useful for surveillance and monitoring activities sensor networks face security challenges in the form of open wireless channel, physical compromise and reprogramming. Due to small sizes and open deployment, compromise attacks are most destructive kind of attacks in Wireless Sensor Networks (WSNs). With applications of WSNs growing from physical surveillance to applications in medical sciences and health monitoring, it is important to investigate specialized security solutions for WSNs. In this thesis we tried to address security challenge by devising key management and secure routing scheme. In this thesis we are using deployment driven localization of security information for the development of scalable key management schemes which are resilient to node compromise and node replication attacks. Using security aware selection of next hop towards destination we designed secure routing schemes. We suggested use of mobile sensors for secure data collection in large sensor networks and addressed authentication and re-authentication of mobile sensors. To meet the requirement of multiple and equally secure paths in a query oriented WSNs, we developed a secure multipath routing scheme. The parameter considered for routing protocols is inclusive resilience, which is improved by increasing link keys on each hop in route. We consider Heterogeneous Wireless Sensor Networks (HWSNs) in which few sensors equipped for high end processing. Computation intensive and organizational activities of HWSNs are iv categorically assigned to high end sensors. The developed schemes/protocols are validated through simulation and analytical modeling.
PhD, CSED, Thesis
Keywords: Heterogeneous; Multipath; Resilience; Localization; Compromise Attack; Computer science